Theoretical Aspects of Location Theory - Paweł ŁOPATKA; Aleksandra RABCZUN (Communications of International Proceedings, 2021)
Location means the location of a given activity in a specific place. The activities of people and business entities take place in a specific place. The very concept of location is often used in economic sciences and is treated as a procedure for selecting a place to conduct a specific economic activity. A specific place has specific location advantages, and each business activity has specific location requirements. In a situation where the values ​​and requirements are best matched to each other, the optimal location for running a business can be determined. The theory of location deals precisely with the study of the causes of the development of economic activity in specific places to provide the basis for research on regional development. The authors express the view that it is worth looking at the development of the theory of location and its contemporary modifications to better understand the issue of regional development. The article aims to analyze the genesis of the location theory and its further evolution. This article reviews the research and the most important papers contributing to the development of the theory of location in economic sciences. The main research method used in the text is the critical analysis of the literature.
Keywords: Location theory; modern location theories; regional development; spatial policy